Dependence of HSP27 cellular level on protein kinase CK2 discloses novel therapeutic strategies - Borgo, Christian; Vilardell, Jordi; Bosello-Travain, Valentina; Pinna, Lorenzo A.; Venerando, Andrea; Salvi, Mauro (Biochimica et biophysica acta. General subjects, 2018)
HSP27 plays a role in various diseases, including neurodegenerative diseases, ischemia, and atherosclerosis. It is particularly important in the regulation of the development, progression and metastasis of cancer as well as cell apoptosis and drug resistance. However, the absence of an ATP binding domain, that is, instead, present in other HSPs such as HSP90 and HSP70, hampers the development of small molecules as inhibitors of HSP27. Knockout cell lines generated by Crispr/Cas9 gene editing tool, specific kinase inhibitors and siRNA transfections were exploited to demonstrate that the expression of HSP27 is dependent on the integrity/activity of protein kinase CK2 holoenzyme. The interaction between these proteins has been confirmed by co-immunoprecipitation, confocal immunofluorescence microscopy, and by density gradient separation of protein complexes. Finally, using a proliferation assay this study demonstrates the potential efficacy of a combinatory therapy of heath shock and CK2 inhibitors in cancer treatment. Our data demonstrate that CK2 is able to regulate HSP27 turnover by affecting the expression of its ubiquitin ligase SMURF2 (Smad ubiquitination regulatory factor 2). Moreover, for the first time we show an increased sensitivity of CK2-inhibited tumour cells to hyperthermia treatment. Being HSP27 involved in several pathological conditions, including protein conformational diseases (i.e Cystic Fibrosis) and cancer, the need of drugs to modulate its activity is growing and CK2-targeting could represent a new strategy to reduce cellular HSP27 level. This study identifies CK2 as a molecular target to control HSP27 cellular expression. •HSP27 cellular level is regulated by protein kinase CK2.•HSP27 is not a CK2 direct substrate.•CK2 controls HSP27 protein level via SMURF2.•A combination of CK2 inhibition and thermotherapy for cancer treatment is proposed.